1988
DOI: 10.1002/jcb.240360306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mutations affecting Na+:H+ antiport activity on tumorigenic potential of hamster lung fibroblasts

Abstract: Mutants unable to regulate intracellular pH through the Na+: H+ antiport system were found to evolve tumors less frequently than wild-type CCL39 hamster lung fibroblasts, after transplantation in athymic nude mice. When rare tumors arose, they comprised cells which were transformed in vitro, but which upon retransplantation grew at a lower rate than tumor cells originating from CCL39 cells. Both parental and mutant cells became transformed after transfection of the activated Harvey ras oncogene, but transfecta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 27 publications
0
25
0
1
Order By: Relevance
“…NHE1 is involved in tumorigenesis, as deletion of this protein drastically reduces tumour growth 82 . The same effects have been observed using pharmacological inhibitors 6,83 such as amiloride or cariporide 84 (compound 23 and 24; FIG.…”
Section: Inhibiting Other Hcomentioning
confidence: 99%
“…NHE1 is involved in tumorigenesis, as deletion of this protein drastically reduces tumour growth 82 . The same effects have been observed using pharmacological inhibitors 6,83 such as amiloride or cariporide 84 (compound 23 and 24; FIG.…”
Section: Inhibiting Other Hcomentioning
confidence: 99%
“…A role for NHE1 in cancer was first reported almost thirty years ago by Pouysségur's group who observed that NHE1-deficient hamster lung fibroblasts formed fewer xenograft tumours in athymic nude mice in comparison to cells expressing the wild-type exchanger (68).…”
Section: Beyond "Housekeeping": Nhe1's Definitive Role In Triple-negamentioning
confidence: 99%
“…The earliest evidence that NHE1 could play a role in cancer stems from the group of Pouysségur and coworkers. In athymic nude mice, injection of CCL39 hamster lung fibroblasts deficient in NHE1 caused tumors less frequently than CCL39 cells with functional NHE1 [83]. Since these initial observations, numerous studies have examined the role of NHE1 in cancer.…”
Section: Slc9a1-nhe1mentioning
confidence: 99%